Generalized lymphogenous metastasis involving parenchymal organs in gastric cancer (case report) - M. V. Zavyalova; A. V. Zavyalov; E. S. Pudova; I. G. Kutsenko; M. A. Egunova; K. A. Klyaus; D. A. Orel; S. V. Vtorushin; V. M. Perelmuter (Сибирский онкологический журнал, 2025)
Generalized metastases to parenchymatous organs in gastric cancer are usually associated with hematogenous spread of cancer cells. Generalized lymphogenous metastasis involves the spread of cancer cells to distant lymph nodes and serous membranes. There is very little information on generalized metastases to parenchymatous organs due to tumor embolism of their lymphatic vessels. Objective: to present a fatal case with generalized lymphogenous metastases to parenchymatous organs. Case presentation. A 56-year-old female patient with gastric cancer presented to the hospital with generalized lymphogenous metastases to parenchymatous organs. The patient received palliative treatment in the hospital for 11 days. The pathological examination showed extensive lymphovascular invasion with massive embolism of the lymphatic vessels of the peritoneum, pleura, pericardium, retroperitoneal tissue and almost all organs except the brain. Tumor emboli in the lymphatic vessels intensively expressed integrin subunits a6 and b4, as well as the laminin subunit γ2. Conclusion. Widespread metastases to parenchymatous organs may be caused by tumor embolism of the lymphatic vessels. This variant of progression may be associated with the expression of integrin subunits α6 and β4, as well as the laminin subunit γ2 by tumor cells.